2010
DOI: 10.1038/jid.2010.218
|View full text |Cite
|
Sign up to set email alerts
|

Japanese-Specific Filaggrin Gene Mutations in Japanese Patients Suffering from Atopic Eczema and Asthma

Abstract: Abbreviations: AE, atopic eczema; CI, confidence interval; Con, healthy control; OR, odds ratio. For combined genotype: asthma+AE, exact P-value of Pearson w 2 -test=0.0122, OR and 95% CI for dominant models (AA vs aX)=7.3692 (1.7715-30.6748); asthmaÀAE, exact P-value of Pearson w 2 -test=0.5563, OR and 95% CI for dominant models (AA vs aX)=1.6124 (0.4979-5.2219); all asthma, exact P-value of Pearson w 2 -test=0.1968, OR and 95% CI for dominant models (AA vs aX)=2.2523 (0.7609-6.6667).www.jidonline.org 2835 R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 10 publications
2
39
0
Order By: Relevance
“…Of asthma patients complicated by AD, 22.2 % carried one or more FLG mutations; 5.9 % of asthma patients without AD carried one or more FLG mutations. It was confi rmed that in Japan there was a strong association between FLG mutations and AD with or without asthma and between FLG mutations and asthma patients who had AD [ 23 ]. However, no association between asthma and FLG mutations was identifi ed.…”
Section: Japanesementioning
confidence: 94%
“…Of asthma patients complicated by AD, 22.2 % carried one or more FLG mutations; 5.9 % of asthma patients without AD carried one or more FLG mutations. It was confi rmed that in Japan there was a strong association between FLG mutations and AD with or without asthma and between FLG mutations and asthma patients who had AD [ 23 ]. However, no association between asthma and FLG mutations was identifi ed.…”
Section: Japanesementioning
confidence: 94%
“…Particularly the study by Wang et al found that the P478S GG genotype signifi cantly increased the risk of developing asthma in patients with AD, OR = 4.68 (1.37-16.03). Moreover, Osawa and co-workers studied FLG mutations in patients with AD and asthma, respectively, and found an increased risk of asthma in Japanese-specifi c FLG mutation carriers [ 33 ].…”
Section: Populations Of Non-european Descentmentioning
confidence: 99%
“…American, (45) Caucasian and Northern-American AD, (2) European and Asian ancestry, (43,(46)(47)(48)(49)(50)(51) Chinese, (52) German, (53) Irish, (43) and Japanese. (54) More than 40 FLG loss-of-function mutations have been described in Europeans and Asians. (43) While in African-American children with AD revealed a total of 289 variants in FLG, 107 variants in FLG2, 339 variants in HRNR, 4 variants in RPTN, 37 variants in CRNN, 88 variants in TCHH, and 14 variants in TCHHL1.…”
Section: -Filaggrin Genementioning
confidence: 99%